Keletas baltų ir slavų kalbų "semti" reikšmės veiksmažodžių ir jų kilmė - Karaliūnas, Simas (Baltistica, 1990)
SOME BALTIC AND SLAVIC VERBS DENOTING “DRAW, SCOOP” AND THEIR ORIGINSome evidence (cf. Lith. griẽbti,  griẽti, kabìnti, kaũšti, kõpti, Lith. kriẽti : Latv. krìet, Pr. kniēipe : Lith. kniẽpti, kneĩpti) indicates that the meaning “draw, scoop” is historically connected with the meaning “take, grasp, pick up”, on the one hand, and with the meaning “fasten, tack, clasp, press together, link, bind”, on the other. On this basis it is assumed that the etymological counterpart of Sl. *čъrрǫ, *čerpti “draw, scoop” is most likely Lith. kér̃pti (-ia) “bind, tie up”; Latv. smel̂t (smeļu, smêlu) “draw, scoop” belongs probably to the root *mel- “bind, tie, link” (with the “movable” s-), contained in Latv. sa-mel̂t (-meļu, -mêlu) “tie together, couple”, Tokh. AB mälk-, A malk- “join”, Hit. malk-, malkii̯a- “turn, twist together, spin” (
Keywords: baltų; slavų; veiksmažodžiai; leksika; semti